Facade-Integrated Semi-Active Vibration Control for Wind-Excited Super-Slender Tall Buildings. Issue 2 (2020) - Zhang, Yangwen; Schauer, Thomas; Wernicke, Laurenz; Wulff, Wulf; Bleicher, Achim
Abstract: Nowadays, skyscrapers are getting higher and more slender due to inner-city concentration, which makes the structure more susceptible to dynamic excitations. The design of super-slender skyscrapers is governed primarily by wind excitation. A traditional Tuned Mass Damper (TMD) has been installed in many skyscrapers to mitigate wind-induced vibrations, which has been proven to be very reliable. However, it needs large additional mass and huge installation space near the top of the building, which makes TMD not optimal for super-slender skyscrapers. In this paper, a semi-active distributed-Multiple Tuned Facade Damper (d-MTFD) using movable facade elements as damping mass is investigated. The facade elements at the upper stories of the building are parallel movable to the primary structure. Electrical Machines (EM) as variable damper are integrated in their connections to realize semi-active vibration control, which makes the system more effective and robust. For real application, a practical design criterion is that the relative displacement of the facade elements cannot be too large, otherwise it makes the occupants feel uncomfortable. Therefore, multi-objective Genetic Algorithm (GA)-optimized on-off groundhook semi-active control is applied, where two control objectives are optimized. One control objective is to minimize the peak top floor acceleration and the other control objective is to minimize the maximum peak relative displacement of all the facade elements. As a result, a Pareto Front shows that better vibration suppression performance and smaller facade relative displacement can be achieved using the multi-objective optimized controller.